DNA damage and Cell Cycle Dysregulation by ATM-P53-GADD45A Pathway in Bleomycin Treated Cervical Cancer Cells - Somi Shrivastava; Ratnacaram Chandrahas Koumar (South Eastern European Journal of Public Health, 2025)
Background Cervical cancer is one of the most prevalent malignancies in women worldwide, yet the underlying mechanism of disease progression still remains unclear. The role of TGF-β1 and GADD45A and its implication in cervical cancer remains elusive. The present study aimed to elucidate the regulatory mechanisms induced by bleomycin in SiHa cells, to identify therapeutics target of DDR pathway. Methods In cervical cancer SiHa cells, different assays were employed to quantify the viability, anti-proliferative and anti-migratory effect of bleomycin. Differential gene expression related to cell cycle, DNA damage response, apoptosis was done by qRT-PCR with bleomycin intervention. Propidium iodide staining was done to confirm DNA damage. The relation of protein interaction with GADD45A was done by protein-protein interaction network. Results Our results emphasises that, bleomycin treatment of SiHa cells significantly inhibits cell proliferation, migration and invasion. Downregulation of CDK1, Cyclin A and Cyclin B genes, induced cell cycle arrest at G2/M phase, confirmed by qRT-PCR and flowcytometry analysis. Significant upregulation of p53, ATM and GADD45A related to DDR and BAX/BCL2 for apoptosis, was confirmed by qRT-PCR. Propidium iodide staining validated the chromatin fragmentation and apoptosis in SiHa cells treated with bleomycin. Conclusion We emphasize that in cervical cancer, bleomycin can be a potent antitumor drug targeting multiple pathways inducing cell cycle arrest, DDR and apoptosis.